Protein pyrophosphorylation by inositol phosphates: a novel post-translational modification in plants? - Mihiret, Yeshambel Emewodih; Schaaf, Gabriel; Kamleitner, Marília (Frontiers in Plant Science, 2024)
Inositol pyrophosphates (PP-InsPs) are energy-rich molecules harboring one or more diphosphate moieties. PP-InsPs are found in all eukaryotes evaluated and their functional versatility is reflected in the various cellular events in which they take part. These include, among others, insulin signaling and intracellular trafficking in mammals, as well as innate immunity and hormone and phosphate signaling in plants. The molecular mechanisms by which PP-InsPs exert such functions are proposed to rely on the allosteric regulation via direct binding to proteins, by competing with other ligands, or by protein pyrophosphorylation. The latter is the focus of this review, where we outline a historical perspective surrounding the first findings, almost 20 years ago, that certain proteins can be phosphorylated by PP-InsPs in vitro. Strikingly, in vitro phosphorylation occurs by an apparent enzyme-independent but Mg 2+ -dependent transfer of the β-phosphoryl group of an inositol pyrophosphate to an already phosphorylated serine residue at Glu/Asp-rich protein regions. Ribosome biogenesis, vesicle trafficking and transcription are among the cellular events suggested to be modulated by protein pyrophosphorylation in yeast and mammals. Here we discuss the latest efforts in identifying targets of protein pyrophosphorylation, pointing out the methodological challenges that have hindered the full understanding of this unique posttranslational modification, and focusing on the latest advances in mass spectrometry that finally provided convincing evidence that PP-InsP-mediated pyrophosphorylation also occurs in vivo. We also speculate about the relevance of this post-translational modification in plants in a discussion centered around the protein kinase CK2, whose activity is critical for pyrophosphorylation of animal and yeast proteins. This enzyme is widely present in plant species and several of its functions overlap with those of PP-InsPs. Until now, there is virtually no data on pyrophosphorylation of plant proteins, which is an exciting field that remains to be explored.